FORMATION KINETICS OF SIMPLE CARBON DIOXIDE AND METHANE HYDRATE AND MIXED C02 - CH4 HYDRATE IN PRESENCE OF PROMOTERS - ABDUL MALIK, SITINURMALA (2014)
The presence of high C02 up to 70% in certain natural gas reservoirs has posted huge challenges in the natural gas purification. Although there are several separation technologies like amine absorption and cryogenic process, their separation capability is limited to low CO2 in natural gas. Alternative approach to separate high CO2 from natural gas by formation of CO2 hydrate is being explored in this work. The objectives are to investigate the formation kinetics of simple and mixed hydrate of carbon dioxide and methane in presence of SDS and POM and the effect of these promoters at various concentrations. Besides that, this study is also conducted to investigate the selectivity of the promoters towards CO2 from natural gas via formation of CO2 hydrates. A laboratory - scale batch reactor is built and operated to carry out this experimental work. In the experimental work, the formation of carbon dioxide hydrate in deionized water (18M£2) is investigated at fixed temperature of 275.15 K and pressure of 20, 25, 30,35 bar respectively. Meanwhile, the formation of methane hydrate in deionized water (18MQ) is investigated at fixed temperature of 273.15 and pressures of 40, 50, 55, 60, 65 bar, respectively.